APPLICATION OF FOURIER TRANSFORM INFRARED SPECTROSCOPY FOR QUALITY CONTROL OF PHARMACEUTICAL PRODUCTS: A REVIEW - Abdul Rahman (Indonesian Journal of Pharmacy, 2012)
Analysis  of  pharmaceutical  products  covers  all  aspects  of quality  control  of  active  pharmaceutical  ingredients  (API)  and finished  products.  Today,  Fourier  transform  infrared  (FTIR)spectroscopy, especially in combination with chemometrics software, has  emerged  as  one  of  the romising  analytical  techniques  to  be used  in  pharmaceutical  industry,  for  quality  control  of  desired pharmaceutical  products.  Compared  with  other  instrumental techniques, FTIR spectroscopy offers  some advantages,  namely  it  is rapid,  simple  in  sample  preparation,  and  not  destructive.  In  this review,  the  application  of  FTIR  spectroscopy  for  qualitative  and quantitative  determinations  of  API  and  monitoring  drug  release  are described.Key words: FTIR spectroscopy, quality control, pharmaceutical products.